THE EFFECT OF THE COLLABORATIVE POMODORO TECHNIQUE AND QUR’ANIC MUROTTAL ON STUDENTS’ LEARNING MOTIVATION IN BIOLOGY LESSONS - Annisa Tri Damayanti; Alimuddin Ali; Asham Bin Jamaluddin; Firdaus Daud; Mushawwir Taiyeb (Jurnal Ilmiah Didaktika, 2026)
This study employed a quasi-experimental design to analyze the implementation of a collaborative approach combining the Pomodoro Technique and Qur’anic murottal recitation on students’ motivation in Biology learning. The research population comprised all eleventh-grade students, and the sampling technique used was saturation sampling because the population was fewer than 100 students. The sample consisted of three classes: Class XI-C as Experimental Group I, which received the combined treatment of the Pomodoro Technique and Qur’anic murottal recitation; Class XI-B as Experimental Group II, which received the Pomodoro Technique treatment; and Class XI-A as Experimental Group III, which received the Qur’anic murottal recitation treatment. The data were analyzed using descriptive and inferential statistics through an ANCOVA test with the assistance of SPSS at a significance level of 0.05. The results of the analysis indicated that learning motivation yielded a p-value of 0.072. Therefore, it can be concluded that the collaboration between the Pomodoro Technique and Qur’anic murottal recitation did not have a statistically significant effect on students' learning motivation, nor was its implementation substantially different. This finding is influenced by the school environment, which possesses a strong academic and religious atmosphere, thereby familiarizing students with spiritually integrated learning. In addition, all classes demonstrated strong initial motivation, active participation, and enthusiasm throughout the learning process.